2021
DOI: 10.1111/jocd.14033
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ultraviolet radiation on skin photoaging — review of in vitro studies

Abstract: Skin aging involves internal and external processes. Changes occurring as a result of genetic conditions (internal, chronological aging) overlap with aging symptoms stimulated by environmental conditions (extrinsic aging). The most harmful external factor threatening the skin is ultraviolet (UV) radiation. UV radiation consists of three components: UVA (λ = 320−400 nm), UVB (λ = 280−320 nm) and UVC (λ = 100−280 nm). UVC radiation, unlike UVA and UVB radiation, is almost completely absorbed by the ozone layer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
95
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 50 publications
3
95
0
5
Order By: Relevance
“…Human skin is constantly undergoing changes resulting from genetically determined changes in the body overlaid with changes stimulated by extrinsic conditions. The strongest extrinsic factor is UV radiation [ 31 ]. Overexposure to sun radiation causes sunburn, degradation of connective tissue, damage to DNA and decrease in immunological response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human skin is constantly undergoing changes resulting from genetically determined changes in the body overlaid with changes stimulated by extrinsic conditions. The strongest extrinsic factor is UV radiation [ 31 ]. Overexposure to sun radiation causes sunburn, degradation of connective tissue, damage to DNA and decrease in immunological response.…”
Section: Discussionmentioning
confidence: 99%
“…In the course of skin photoaging, an increase in the expression of many MMPs, which degrade ECM proteins, is observed. In addition, MMPs play a key role in photocancerogenesis, affecting various processes associated with tumor progression, such as tumor growth, angiogenesis, and metastasis [ 31 , 77 ]. MMP-2 and MMP-9 are responsible for the degradation of type I collagen (MMP-2), elastin and fibronectin [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the impact of 5G electromagnetic radiation (EMR) on human skin has been drawing attention [ 4 , 5 , 6 ], since the skin interfaces between the body and the external environment and serves as the primary target tissue for EMR from the environment. Indeed, the EMR such as ultraviolet, visible light like blue light and infrared radiation affect the skin physiology significantly [ 7 , 8 , 9 , 10 ], signifying that 5G EMR may also have effects on the skin. Also, it is highly probable that the skin may be the primary target tissue of 5G EMR since 28 GHz EMR from the environment cannot penetrate into our body deeper than 2 mm [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human skin will be exposed to more solar ultraviolet (UV) radiation due to ozone-layer depletion ( Gromkowska Kępka et al, 2021 ; Lyons et al, 2021 ). Although many scientists have tried their best to slow, halt, or reverse the destruction of the ozone layer, such as reducing the emission of chlorofluorocarbons, this recovery process requires several years or even decades ( Krutmann and Berneburg, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Animal experiments have shown that the skin of mice appeared wrinkled, thickened, and stained after exposure to UV radiation for a long time ( Gromkowska Kępka et al, 2021 ). Sharp decreases were observed in skin elasticity, water content, and collagen content (measured by hydroxyproline (HYP)) ( Petruk et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%